Synthesis and Characterization of Uniform Spherical Nanoporous TiO2 Aerogel Templated by Cellulose Alcohol-Gel with Enhanced Photocatalytic Activity - Zhiming Liu; Peng Wu; Shaoli Yang; Haiying Wang; Chunde Jin (International Journal of Polymer Science)
The spherical nanoporous TiO2 aerogels were prepared by a simple ethanol-thermal method, using spherical cellulose alcohol-gel as the template. The morphology, crystalline structure, pore size, specific surface area, and the photocatalytic activity of obtained TiO2 aerogel were separately characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), N2 adsorption-desorption isotherms, and double beam UV-VIS spectrophotometer. The characteristics of TiO2 aerogels presented uniform sphere shape, good internal structural morphology, high specific surface area (ranging from 111.88 to 149.95 m2/g), and good crystalline anatase phase. Moreover, methyl orange dye was used as the target pollutant to characterize the photocatalytic activities and the adsorption performance. The photocatalytic experiment shows that the obtained spherical TiO2 aerogels had a higher degradation ratio of 92.9% on methyl orange dye compared with aspherical TiO2 aerogels prepared from other concentrations of tetrabutyl orthotitanate (TBOT).